2005
DOI: 10.1097/01.tp.0000149322.70295.a5
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Vitamin D3 to Prevent Bone Loss in Renal-Transplant Patients Receiving Low Doses of Steroids

Abstract: Kidney-transplant recipients receiving modern immunosuppressive regimens with low doses of corticosteroids experience only minimal loss of BMD during the first posttransplant year. Cholecalciferol supplementation did not prevent posttransplant bone loss but contributed to the normalization of iPTH levels after renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 32 publications
6
47
2
7
Order By: Relevance
“…Despite hypophosphatemia and hyperparathyroidism, conditions that are known to stimulate increased calcitriol synthesis (21), serum calcitriol levels remain often at the lower range in the early posttransplantation period (38,39). In this study, high calcitriol levels were observed to be independently associated with female gender, good renal function, and high calcidiol and PTH levels.…”
Section: Discussionmentioning
confidence: 50%
“…Despite hypophosphatemia and hyperparathyroidism, conditions that are known to stimulate increased calcitriol synthesis (21), serum calcitriol levels remain often at the lower range in the early posttransplantation period (38,39). In this study, high calcitriol levels were observed to be independently associated with female gender, good renal function, and high calcidiol and PTH levels.…”
Section: Discussionmentioning
confidence: 50%
“…Another important result of this study is to show that lowdose steroid therapy induces minimal bone loss. In our study, different from Wissing et al, [27] low-dose vitamin D3 and calcium supplementation has reduced bone loss and normalized PTH levels.…”
Section: Discussioncontrasting
confidence: 39%
“…[25] On the contrary, Mikuls et al reported only a minor loss of lumbar spine and no loss of femoral neck BMD during the first six posttransplant months in spite of a higher cumulative prednisolone dose of 4.2 g in the same period. [26] In another study by Wissing et al, [27] a single dose of 25,000 IU vitamin D3 monthly implementation had no effect on bone loss but normalized PTH levels on transplantation patients compared with control group. Another important result of this study is to show that lowdose steroid therapy induces minimal bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…60 Studies from our group and other have already shown that cholecalciferol supplementation is a safe way to increase 25 (OH)D concentrations in kidney transplant recipients, but the small number of treated patients included in these studies and their short follow-up do not allow any conclusion on the effect of these treatments on kidney function. [61][62][63] Our results should encourage randomized controlled trials evaluating the effect of early cholecalciferol supplementation on renal allograft function and provide valuable information on the magnitude of the expected effects of such treatments on renal function and histologic features.…”
Section: Discussionmentioning
confidence: 99%